The Implementation of Educandy Towards Students’ Vocabulary Mastery in Fifth-Grade at Elementary School - Ni Putu Utami Riyanthi; Luh Gd Rahayu Budiarta; Ni Wayan Monik Rismadewi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This study aims to determine whether there is a significant effect of the use of Educandy on students’ vocabulary mastery of fifth-grade in elementary school. This study used a quantitative method with a quasi-experimental design. The sampling technique used is total sampling with intact group. The population of this study was all fifth-grade students. The sample used was class 5A as the control group with 32 students, and class 5B as the experimental group with 32 students. The instrument used was a vocabulary test in the form of multiple choices consisting of 20 questions. Data were collected using a pre-test and post-test, and analyzed using the Mann-Whitney test. The results of this study showed that the mean score of the experimental group was higher than the control group. The calculation results of the Mann-Whitney test showed Asymp. Sig. (2-tailed) .001 α = 0.05, which means Ha is accepted and H0 is rejected. The calculation of the effect size also showed that Educandy has a large effect. Therefore, this study concluded that the use of Educandy is effective in mastering the vocabulary of fifth grade students in elementary school.